BUDIDAYA JAMUR PERUSAK KAYU II. PENILAIAN EFISIENSI BIOLOGI PADA MEDIA DARI LIMA BELAS JENIS KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
Oyster  mushroom was cultivated on sawdust media  of  damar (Agathis  sp), durian (Durio  zibethinus Murr.),  teak. (Tectona  grandis  L.f),  jeungjing (Albizia  falcataria  (L.)   Fosb.),   rubber  (Hevea  brasiliensis Muell.  Arg.), coconut  (Cocos nucifera L.),  kemang  (Mangifera  caesia  Jack),   manii (Maesopsis eminii Engl.),   meranti  merah  (Shorea  johorensis Foxw.), nangka  (Artocarpus  integra  Merr.),   pulai  (Alstonia   scholaris R.Br.),    sehiye  (Sterculia macrophylla Vent.),   shiega  (Celtis latifolia Planch.),   sihara (Ganophyllum falcatum BL.)   and pine  (Pinus  merkusii Jung  et  De  Vr.). The  composition   of  the media  was  77,5  % sawdust   mixed   with  20  % rice  bran,   0,5 % lime,  0,5 % trisuperhosphate   and 1,5 % gypsum.  Each media  was mixed   with  distilled   water 125  - 150 % per dry  weight  of  media.  The  media  was  cooled  after  autoclave sterilization    before being  inoculated   with  pure  culture   of  the  mushroom. The  mature   mushroom    was harvested   daily after  the growth  of  the  fruiting  body.  Biological  Efficiency (BE) was calculated  based on the yield  of fresh  mushroom   in proportion  with  the  dry  weight  of  material  used  as media.The  higher BE  was obtained  from  rubber wood   sawdust   media  (86.15  %),  nangka (66.26 %),  kemang  (63,85%) and pulai  (63.52).  The  lowest  BE  was obtained  from damar  (28.22 %).